Validation on proposals for strategic service innovation at automobile service center: a study of automotive service center in Malaysia - Majid, Ahmad Zuhairi Abdul (2012)
This study is looking at specific location of Malaysian automobile service center in Klang valley. The early findings show that most of the customers feel the environment are not giving so much of good experience and also they are lack of information and entertainment values. Structured and unstructured interview questions were posed to selected respondents. A set of questionnaire was constructed through an analysis of keywords from literature reviews. The study described the validation of findings and proposals that versus validity questions. The validation process is important to ensure that the findings and proposals emerged to be agreed or differed by the respondents. The data collected from this validation has gone through factor analysis. Finally, a model representing new fundamental strategy for service innovation design is presented.